Israel-Palestine : lands and peoples - Bartov, Omer (Berghahn, 2021)
"The conflict between Israel and Palestine has raised a plethora of unanswered questions, generated seemingly irreconcilable narratives, and profoundly transformed the land's physical and political geography. This volume seeks to provide a deeper understanding of the links between the region that is now known as Israel and Palestine and its peoples-both those that live there as well as those who relate to it as a mental, mythical, or religious landscape. Engaging the perspectives of a multidisciplinary, international group of scholars, it is an urgent collective reflection on the bonds between people and a place, whether real or imagined, tangible as its stones or ephemeral as the hopes and longings it evokes"--